An Fe–N co-doped tube-in-tube carbon nanostructure used as an efficient catalyst for the electrochemical oxygen reduction reaction. (17th September 2019) - Zhang, Jianshuo; Zhao, Yi; Hou, Kun; Wu, Chuxin; Guan, Lunhui
Abstract: An Fe–N co-doped tube-in-tube carbon nanostructure is synthesized for an efficient oxygen reduction reaction. Thanks to its hollow nature, the mesoporous structure is enriched while defects are not prominent, allowing excellent activity ( E 1/2  = 0.851 V) and durability together with methanol tolerance in an electrochemistry test under alkaline conditions. Furthermore, when the material is used as the cathode catalyst of a Zn–air battery, the battery exhibits a peak power density of 181.5 mW cm −2 .